Lithuanian Obscene Paremias: Peculiarities of Recording and Publication - Vingrys, Martynas (Tautosakos darbai, 2023)
The article deals with obscene paremias in terms of their usage, recording and publication; besides, the prevailing interwar attitude of the society and scholars towards these obscene folklore pieces is also revealed. This empiric study is based on archived materials and articles from interwar periodicals; it strives to reveal several different perspectives, i. e. those of folklore bearers, collectors and researchers. The analysis of the obscene paremias, including certain aspects of using this limitedly public kind of folklore, the history of its collection and publication enabled re-consideration of problematic questions raised by the obscene folk compositions and noting the changing attitude towards this kind of folklore in the nowadays folkloristics. Apparently, the most significant turn in the process of collecting was affected by the guides for folklore collecting published since the 1920s, since they emphasized that various kinds of folklore were worth recording, regardless of their ethical merits. Besides, the folklore collectors were encouraged to record not only the texts of the paremias, but also all the subsidiary information, related to the recorded variants. Observations and commentaries by informants and recorders constitute the very important and nearly the only available materials elucidating the situations of using the obscene paremias. Obviously, changes in the prevailing ideology resulted in shifting character of censoring, along with altered boundaries of morality. For instance, certain paremias considered immoral in the middle of the 19th century, were not censored when reprinted in the beginning of the 20th century. On the other hand, certain words that were considered proper in the 19th century, were censored in the first half of the 20th century. There is still no unanimous and clear agreement on the ways of dealing with the obscene folklore, although with time, researchers’ attitudes shift towards the scholarly objectivity. This shift is obvious in the fundamental collection of the “Lithuanian Proverbs and Proverbial Phrases”, the recent volumes on which include obscene variants of paremias (contrary to the first volumes).